Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.2174/157489106775244073
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Infective Quinone Derivatives of Recent Patents

Abstract: Quinones are important naturally occurring pigments widely distributed in nature and are well known to demonstrate various physiological activities as antimicrobial and anticancer compounds. This review will focus on the preparation, therapeutic application, and administration of several benzoquinones, naphthoquinones, and anthraquinones having anti-infective, e.g. antiviral and antibacterial activities, in recent patents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…Overall yields for this process are moderate. 125 Cimen et al 127 have recently reported TMP to TMQ oxidation with potassium peroxomonosulfate, KHSO 5 , present in oxone catalysed by either iron phthalocyanin tetrasulfonate, [FePcTS] The highlight of the above strategy is that the reaction proceeded with 100% yield when the oxidant:substrate:catalyst molar ratios were 1200:300:1. Phenols with bulky substituents can also be converted to corresponding benzoquinones.…”
Section: Synthesis Of 14-benzoquinones From Phenolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall yields for this process are moderate. 125 Cimen et al 127 have recently reported TMP to TMQ oxidation with potassium peroxomonosulfate, KHSO 5 , present in oxone catalysed by either iron phthalocyanin tetrasulfonate, [FePcTS] The highlight of the above strategy is that the reaction proceeded with 100% yield when the oxidant:substrate:catalyst molar ratios were 1200:300:1. Phenols with bulky substituents can also be converted to corresponding benzoquinones.…”
Section: Synthesis Of 14-benzoquinones From Phenolsmentioning
confidence: 99%
“…3 Their role as electron transfer agents in primary metabolic processes like photosynthesis and respiration is vital to human life. A large number of chemical derivatives with 1,4-benzoquinone as the basic subunit exhibit prominent pharmacological applications such as antibiotic, 4,5 antitumor, [6][7][8][9] antimalarial, 7,10 antineoplastic, 11 anticoagulant 12 and herbicidal activity. 13 Wide applications of quinones can also be found in the field of synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, oxidative stress may be involved as one interpretation of the morphological changes, based on the fact that many quinones generate reactive oxygen species such as oxidative radicals, hydrogen peroxide, and superoxides by redox cycling involving quinones, NADH, and oxygen under aerobic conditions in the cells. 33) In summary, we isolated SPF, which is cytotoxic to rat liver cancer cells, from yellow hornet nests. To our knowledge, this is the first example of the isolation and structural determination of an anticancer quinone molecule from the nest of a social wasp.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that malaria parasite degrades up to 80 % of the haemoglobin in the host cell and releases heme which is toxic to parasite and their host. 17 Neutralization of heme occurs mainly due to hemozoin formation by the parasites. Inhibition of hemozoin formation is, therefore, an important drug target to kill the parasite cell.…”
Section: Antimalarial Activitymentioning
confidence: 99%